Empresa e Comunidade: Responsabilidade Social, Sobrevivência, Produtividade e Imagem Institucional - Souza, Gina Claudia Nadal Nunes de (2000)
Initially, one is presented with a historical overview of the social-political and economic relationships in western society, from the Roman Empire through early capitalism, in order to identify the parties that have been in charge of the welfare of communities. This first section allows one to observe that this task has been handled by the Catholic Church, kings, confraternities, and State-Nations, and that it has been primarily associated with entities that have been in power. Following, current issues are brought to one's attention, as the focus shifts to the way the economic powers, more specifically, the industries offering products and services, perform nowadays as organizations socially responsible for the development of the communities where they have placed their production plants, and to the impact the new marketing and social strategies have on the public image and survival of those industries. In the last section, supported by field work carried out at the Refinaria Duque da Caxias do Sistema Petrobras - REDUC, one is able to examine the relationship established between the company and the local community, by pointing out the reasons that led Refinarias Duque de Caxias to engage in social work through special policies and action plans.